Model Kinetik Amyloid-Beta (Aβ) pada Penyakit Alzheimer Menggunakan Metode Euler dan Runge-Kutta Order ke-4 - Cindyawati, Cindyawati; Ahmad, Faozan; Hardhienata, Hendradi; Kartono, Agus (Jurusan Fisika FMIPA Universitas Andalas, 2025)
Alzheimer's disease (AD) is a neurological disease that causes decreased brain function. It is known that the accumulation of amyloid-beta (Aβ) plaques in the brain is one of the causes of AD. The accumulation of Aβ plaques in the brain is a dynamic process; it begins with the growth of amyloid-beta monomers (M1). Furthermore, amyloid-beta dimers (M2) and so on, so that this collected into oligomers (O), fibrils (P), and plaques in the brain. This disrupts the communication pathways between nerve cells. In this study, each process of amyloid-beta plaque accumulation is presented with a mathematical model in the form of an ordinary differential equation. Therefore, the coupled ordinary differential equations are given for the entire process of Aβ plaque accumulation. In this study, this coupled model is calculated using numerical methods, such as the Euler and fourth-order Runge-Kutta methods. The Euler methods is simple and efficient, but its accuracy is low and can accumulate errors with larger step sizes. The fourth-order Runge-Kutta methods offers higher accuracy, better numerical stability, and greater control over the accuracy of the solution. These two numerical methods have never been compared for estimating numerical solutions of coupled ordinary differential equations.